Against the sacred body: The processing of remains in Catholic circles. (10th June 2021) - Sbardella, Francesca
Abstract : In the Catholic areas of Europe, the human remains (both their bones and the fabrics they touched) of persons considered to have been exceptional are usually stored for transformation into relics. The production and the reproduction of the object-relic takes place within monasteries and is carried out firstly on the material level. In this article I intend to present in detail, from an anthropological standpoint, the practices used to process such remains, the role of the social actors involved and the political-ecclesiastical dynamics connected with them. Owing to obvious difficulties in accessing enclosed communities, such practices are usually overlooked in historiographical and ethno-anthropological analyses, while they should instead be considered the most important moment in the lengthy process intended to give form and meaning to remains, with a view to their exhibition and use in ritual.